Reproductive Health Game (KEPO Game) to the Self-Concept and Adolescent Reproductive Health Motivation - Melly Damayanti; Firman Fuad Wirakusumah; Ruswana Anwar (Global Medical & Health Communication (GMHC), 2018)
The problem of adolescent reproductive health has not been adequately addressed, although there have been many tried attempts both formally and informally. Adolescents aged 12–15 years old are suitable for early reproductive health education, so the needed media that suits their needs and developments. Reproductive health/kesehatan reproduksi (KEPO) game contains information about reproductive health and moral messages in the formation of self-concept, healthy reproduction, health motivation, and responsibility. The purpose of this study was for knowing the effect of using the KEPO game to the self-concept and motivation of adolescent reproductive health. The study layout uses a quasi-experiment with a pretest-posttest with control group design. The treatment group received a KEPO game, while the control group received the Young Health Programme (YHP). This study uses a sampling technique using simple random sampling with a sample of 42 students for each group. The analysis used is the nonparametric test. This research was implemented in the work area of the Public Health Center Ujungberung in Bandung city on the April–May 2017. The results showed that there was an effect of using the KEPO game to self-concept and motivation of adolescent reproductive health (p<0.001). The increase in self-concept in the treatment group was 8.2%, while in the control group it was 2.2%. For reproductive health motivation, the treatment group experienced an increase of 9.5%, while the control group experienced an increase of only 0.8%. Conclusion, the KEPO game increased self-concept and reproductive health motivation in adolescents. GIM KESEHATAN REPRODUKSI (KEPO) UNTUK KONSEP DIRI DAN MOTIVASI KESEHATAN REPRODUKSI REMAJAMasalah kesehatan reproduksi remaja belum teratasi dengan baik, meskipun telah banyak upaya yang dilakukan baik secara formal maupun informal. Remaja usia 12–15 tahun merupakan masa yang tepat untuk pendidikan kesehatan reproduksi secara dini sehingga dibutuhkan media yang sesuai dengan kebutuhan dan perkembangannya. Gim kesehatan reproduksi (KEPO) berisikan informasi tentang kesehatan reproduksi dan pesan moral dalam pembentukan konsep diri dan motivasi kesehatan reproduksi yang sehat serta bertanggung jawab. Tujuan penelitian mengetahui pengaruh penggunaan gim KEPO terhadap konsep diri dan motivasi kesehatan reproduksi remaja. Rancangan penelitian menggunakan quasi-experiment dengan pretest-posttest with control group design. Kelompok perlakuan mendapatkan gim KEPO, sedangkan kelompok kontrol mendapatkan Program Pelayanan Kesehatan Peduli Remaja (PKPR). Teknik pengambilan sampel menggunakan simple random sampling dengan jumlah sampel 42 siswa untuk setiap kelompok. Analisis yang digunakan adalah tes nonparametrik. Penelitian ini dilakukan di wilayah kerja Puskesmas Ujungberung Kota Bandung pada bulan April–Mei 2017. Hasil penelitian menunjukkan terdapat pengaruh penggunaan gim KEPO terhadap konsep diri dan motivasi kesehatan reproduksi remaja (p<0,001). Kenaikan konsep diri pada kelompok perlakuan 8,2%, sedangkan pada kelompok kontrol 2,2%. Untuk motivasi kesehatan reproduksi pada kelompok perlakuan mengalami kenaikan 9,5%, sedangkan kelompok kontrol mengalami peningkatan hanya 0,8%. Simpulan, gim KEPO meningkatkan konsep diri dan motivasi kesehatan reproduksi remaja.